2022
DOI: 10.1108/ijbm-04-2022-0147
|View full text |Cite
|
Sign up to set email alerts
|

Young adults' financial well-being: current insights and future directions

Abstract: PurposeFinancial well-being among young adults is an emerging and important field of research. This study aims to shed light on the current insights and future directions for young adults’ financial well-being research.Design/methodology/approachA systematic review was performed using (1) the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol to curate the corpus and (2) the bibliometric-content analysis technique to review that corpus on young adults’ financial well-being research.Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 117 publications
(356 reference statements)
2
24
0
1
Order By: Relevance
“…In addition to that, past studies have also indicated positive associations between subjective financial knowledge, financial behaviour and financial well-being (Riitsalu and Murakas, 2019). Particularly, financial behaviour often acts as a mediator in the relationship between financial knowledge and financial well-being (Saurabh and Nandan, 2018;She et al, 2022b;Totenhagen et al, 2019). Thus, when there is a positive association between future time perspectives and financial well-being (Kooij et al, 2018;Rutledge and Deshpande, 2015;Yu et al, 2015), a novel mediating path through goal clarity, financial knowledge and responsible behaviours, is suggested to be examined.…”
Section: Responsible Financial Behaviour and Financial Well-beingmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to that, past studies have also indicated positive associations between subjective financial knowledge, financial behaviour and financial well-being (Riitsalu and Murakas, 2019). Particularly, financial behaviour often acts as a mediator in the relationship between financial knowledge and financial well-being (Saurabh and Nandan, 2018;She et al, 2022b;Totenhagen et al, 2019). Thus, when there is a positive association between future time perspectives and financial well-being (Kooij et al, 2018;Rutledge and Deshpande, 2015;Yu et al, 2015), a novel mediating path through goal clarity, financial knowledge and responsible behaviours, is suggested to be examined.…”
Section: Responsible Financial Behaviour and Financial Well-beingmentioning
confidence: 99%
“…In addition to that, past studies have also indicated positive associations between subjective financial knowledge, financial behaviour and financial well-being (Riitsalu and Murakas, 2019). Particularly, financial behaviour often acts as a mediator in the relationship between financial knowledge and financial well-being (Saurabh and Nandan, 2018; She et al ., 2022b; Totenhagen et al ., 2019).…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, economic prosperity is a crucial predictor of overall well‐being (MacDonald & Douthitt, 1992; Netemeyer et al., 2018; She et al., 2022). Financial literacy protects consumer well‐being during a pandemic.…”
Section: Introductionmentioning
confidence: 99%